Social listening and crowdsourcing in disaster communication—A citizen-centered media and communication consumption perspective - Andersen, Nina Blom; Hill, Louise; Baron, Nina; Nielsen, Anne Bach (Frontiers in Communication, 2025)
To secure more resilient communities in the future, it is essential to strengthen the links between all actors. Communication and active engagement are tools to do so. Based on a case study of communication practices in relation to disasters and emergencies in a Danish urban setting, this article examines the potential of applying the principles of crowdsourcing and active social listening to enhance the links between disaster management organizations and citizens. The case study is based on a triangulation of expert interviews with representatives from disaster management organizations, focus groups and surveys with citizens, as well as a media ethnographic study of interactions and conversations on local social media. The study finds that some organizations are already applying principles of crowdsourcing and active social listening, but there is a need to consider local context and media consumption in order to succeed. The study shows that though the majority of the residents in the case community are very digitalized, there are at least two obstacles for digital crowdsourcing and social listening in this setting: firstly the preferred social media is not suited for digital crowdsourcing and secondly the residents prefer to communicate through a variety of other platforms and networks as well, where digital crowdsourcing and social listening is not possible. Based on those findings, this article discusses methods to apply in addition to the digital ones to further strengthen the relations between disaster management organizations and citizens.